(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
Consumers around the world are bombarded with too many options of products which are either new or seems to be new .Consumers, therefore feel that they are a part of marketing arena where either the products or schemes related to them are making life miserable. Permission Marketing (PM), which emphasise on seeking permission first and then dissemenation of marketing messages has become the need of hour. PM practices which are technology driven either by mobile technology or internet technology give respite to consumers by allowing permitted marketing messages. Present study is based on secondary data which had been collected from various sources like Book Reviews of book authored by Seth Godin, Review Reports, Survey Reports of Telecom Regulaory Authority of India (TRAI) , Marketing White Book and various other reports.The data available in various dissertations ,research papers and articles have been also utilized by the accession of DELNET and EBESCO. This paper will emphasise on how by using mobile and inernet technology , Indian consumers can make a better decision keeping their choice in consideration. This paper is useful for marketing professionals who are in the business of marketing of various goods and services by highlighting the future research directions in this bizarre area.